Carbon-coated slurry for current collector, preparation method of carbon-coated slurry, carbon-coated current collector, positive plate and battery
By adding diisocyanate and azodicyanovaleric acid to the carbon coated slurry to form hydrogen bonds and covalent bonds, the problem that traditional carbon coated aluminum foil is difficult to meet the peeling force requirements of the positive electrode sheet of lithium-ion batteries is solved, and the cycling performance and capacity retention rate of the battery cell are significantly improved.
Patent Information
- Application Number
- CN202510084135.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-25
AI Technical Summary
Traditional carbon-coated aluminum foils are difficult to meet the peeling force requirements of the positive electrode sheet of lithium-ion batteries, affecting the process stability and cycling performance of the battery cell.
By adding diisocyanate and azodicyanovaleric acid to the carbon coating slurry, hydrogen bonds and covalent bonds are formed to enhance the peeling force of the positive electrode sheet.
It significantly improves the peeling force of the positive electrode sheet, improves the cycling performance and capacity retention rate of the battery cell, and ensures the electrical performance and life of the battery.
Smart Images

Figure CN119875531A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a current collector carbon-coated slurry and a preparation method thereof, a carbon-coated current collector, a positive electrode sheet and a battery. Background Art
[0002] Currently, the most popular and rapidly developing batteries include lithium-ion batteries and sodium-ion batteries. Among them, lithium-ion batteries are widely used in many electronic technology fields including computers, automobiles and mobile phones due to their many advantages such as high energy density, wide operating temperature range, long stable discharge storage time, long storage and cycle time, etc.
[0003] This type of battery is mainly composed of four key materials: positive and negative electrode materials, electrolyte and separator. As the requirements for battery cell performance increase, the improvement of the positive electrode sheet peeling force has become the main demand of customers, but traditional carbon-coated aluminum foil is difficult to meet the peeling force requirements, so it is necessary to further optimize and improve the peeling force of carbon-coated aluminum foil on the positive electrode sheet to ensure the process stability and battery cell cycle performance after the carbon-coated slurry is applied. Summary of the invention
[0004] The purpose of the present invention is to solve the above problems and provide a current collector carbon-coated slurry and a preparation method thereof, a carbon-coated current collector, a positive electrode sheet and a battery to improve the peeling force of the battery electrode sheet.
[0005] To achieve the above purpose, the technical solution provided by the present invention is:
[0006] A first aspect of the present application provides a current collector carbon coating slurry, wherein the carbon coating slurry contains diisocyanate and azobiscyanovaleric acid.
[0007] The carbon coating slurry contains a binder, the diisocyanate and azobiscyanovaleric acid are added to the binder and the binder is mixed with the carbon coating material to obtain the carbon coating slurry; the carbon coating material is selected from at least one of conductive carbon powder and graphite.
[0008] A second aspect of the present application provides a method for preparing a current collector carbon-coated slurry, comprising the following steps:
[0009] Adding diisocyanate and azobiscyanovaleric acid into the binder aqueous solution to prepare a modified binder;
[0010] The modified binder is mixed with a carbon-coated material to form a carbon-coated slurry.
[0011] To optimize the above technical solutions, the specific measures taken also include:
[0012] The binder is selected from at least one of polyacrylic acid, styrene-butadiene latex, polyacrylonitrile and polyurethane. When preparing the binder aqueous solution, the binder and water are mixed in proportion and dispersed evenly, and heated and kept warm for reaction.
[0013] Preferably, the mixing mass ratio of the binder to water is 2-5:10, and the heating and heat preservation reaction temperature is 80-100°C; after the binder aqueous solution is cooled to 50-70°C and the temperature is stable, diisocyanate is added, and the reaction is continued by heat preservation and stirring for 1-5 hours, and then the temperature is lowered to 20-30°C, and azobiscyanovaleric acid is added.
[0014] Furthermore, a water-resistant additive is added to the binder aqueous solution, and the water-resistant additive is added after the azobiscyanovaleric acid is added; the mass percentage of the water-resistant additive added to the binder aqueous solution is 0.05-0.5%.
[0015] Preferably, in the aqueous binder solution, the added mass percentage of diisocyanate is 0.1-5%, and the added mass percentage of azobiscyanovaleric acid is 0.05-0.1%; the mixing mass ratio of the binder to the conductive carbon powder and graphite is 20-50:30-60:0.1-2.
[0016] The third aspect of the present application provides a carbon-coated current collector, which has a carbon-coated layer formed on a current collector foil by the above-mentioned carbon-coated slurry.
[0017] The fourth aspect of the present application provides a positive electrode sheet comprising the above-mentioned carbon-coated current collector.
[0018] The fifth aspect of the present application provides a battery comprising the above-mentioned positive electrode sheet.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The present invention provides a current collector carbon coating slurry and a preparation method thereof, a carbon coated current collector, a positive electrode sheet and a battery. The stripping force of the positive electrode sheet is improved by adding diisocyanate and azobiscyanovaleric acid to the carbon coating slurry.
[0021] In the current collector carbon coating slurry of the present invention, atoms with strong electronegativity are introduced by adding diisocyanate, so that hydrogen bonds are formed between the carbon coating slurry and the positive electrode binder polyvinylidene fluoride resin PVDF on the positive electrode sheet; by adding azobiscyanovaleric acid, during the coating and baking process of the carbon coating slurry, the positive electrode binder polyvinylidene fluoride resin PVDF of the positive electrode sheet and the binder on the surface of the carbon coating layer are dissolved in each other, and covalent bonds are formed through the cross-linking effect of diisocyanate and azobiscyanovaleric acid, which significantly improves the peeling force of the electrode sheet formed after the carbon coating slurry is coated and rolled, thereby effectively improving the cycle performance of the battery cell and the capacity retention rate of the battery cell; the present invention further strengthens the cross-linking reaction between diisocyanate and azobiscyanovaleric acid and the positive electrode sheet by adding a water-resistant additive.
[0022] The scheme of the present invention can ensure the uniformity of the positive electrode peeling force, improve the electrical performance and life of the battery, ensure the stability of the battery during cyclic charge and discharge, and greatly improve the processing performance during the coating of the positive electrode active material. Due to the high peeling force, during the winding and rolling transportation process, the positive electrode active material is tightly bonded to the current collector and is not easy to fall off. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 : Flow chart of the preparation method of the current collector carbon-coated slurry of the present invention.
[0024] Figure 2 : An electron microscope image of the current collector of the present invention after roller pressing with the positive electrode active material. DETAILED DESCRIPTION
[0025] The above contents of the present invention are further described in detail below in the form of embodiments, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following embodiments, and all technologies realized based on the above contents of the present invention belong to the scope of the present invention.
[0026] The experimental methods used in the following examples are all conventional methods unless otherwise specified, and the reagents, methods and equipment used are all conventional reagents, methods and equipment in the technical field unless otherwise specified.
[0027] For the sake of simplicity, this document only specifically discloses some numerical values and optional ranges. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range. Similarly, any upper limit can be combined with any other upper limit to form an unambiguous range; the optional items in the optional range can also be combined arbitrarily.
[0028] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art.
[0029] The present application provides a current collector carbon coating slurry, wherein the carbon coating slurry contains diisocyanate and azobiscyanovaleric acid.
[0030] The carbon coating slurry contains a binder, and diisocyanate and azobiscyanovaleric acid are added to the binder and the binder is mixed with the carbon coating material to obtain the carbon coating slurry;
[0031] The carbon-coated materials in the present application include but are not limited to conductive carbon powder or graphite, single-walled carbon nanotubes, multi-walled carbon nanotubes, and graphene.
[0032] The present application also provides a method for preparing a current collector carbon-coated slurry, comprising the following steps:
[0033] Adding diisocyanate and azobiscyanovaleric acid into the binder aqueous solution to prepare a modified binder;
[0034] The modified binder is mixed with the carbon-coated material to form a carbon-coated slurry.
[0035] The binder is selected from at least one of polyacrylic acid, styrene-butadiene latex, polyacrylonitrile and polyurethane.
[0036] In some embodiments, when preparing the binder aqueous solution, the binder and water are mixed in proportion and dispersed evenly, and heated and kept warm for reaction; the mixing ratio of the binder to water is 2 to 5:10.
[0037] Specifically, the stirring speed of the blending, dissolving and dispersing is 10 to 50 rpm, the heating temperature is 80 to 100° C., and the heat preservation reaction time is 0.5 to 3 hours.
[0038] Specifically, the binder aqueous solution is cooled to 50-70° C., stirred at 30-100 rpm, and diisocyanate is added after the temperature stabilizes; after the reaction is continued for 1-5 hours with heat preservation and stirring, the temperature is lowered to 20-30° C., and azobiscyanovaleric acid is added.
[0039] In some embodiments, a water-resistant additive is further added to the binder aqueous solution, and the water-resistant additive is added after the azobiscyanovaleric acid is added; in the binder aqueous solution, the added mass percentage of the water-resistant additive is 0.05-0.5%, and the water-resistant additive is selected from maleic anhydride (MA), sodium sulfonate, and trimellitic anhydride by way of non-limiting examples.
[0040] In some embodiments, in the aqueous binder solution, the added mass percentage of diisocyanate is 0.1-5%, and the added mass percentage of azobiscyanovaleric acid is 0.05-0.1%.
[0041] In some embodiments, the mixing mass ratio of the binder to the conductive carbon powder and graphite is 20-50:30-60:0.1-2.
[0042] In some embodiments, after the modified binder is mixed with the carbon-coated material, the mixture is stirred at 2000-5000 rpm to obtain a carbon-coated slurry.
[0043] The present application also provides a carbon-coated current collector, which has a carbon-coated layer formed on a current collector foil by the above-mentioned carbon-coated slurry.
[0044] In some embodiments, the carbon-coated slurry is ground before being coated on the surface of the current collector foil; preferably, the grinding is performed using a sand mill with a grinding time of 0.5-3 hours and a grinding speed of 500-1200 rpm.
[0045] In some embodiments, the carbon-coated slurry is coated on the surface of the current collector foil and then dried; preferably, the drying process is to remove moisture through a coating baking process, the baking temperature is 40-80° C., and the baking time is 1-3 min.
[0046] In some embodiments, the coating method includes but is not limited to micro-concave roller coating and spray coating.
[0047] The present application also provides a positive electrode sheet comprising the above-mentioned carbon-coated current collector.
[0048] The present application also provides a battery comprising the above-mentioned positive electrode sheet.
[0049] The present invention is further described in detail below in conjunction with specific embodiments:
[0050] Example 1
[0051] 6 kg of polyacrylic acid was blended with 20 kg of deionized water to fully dissolve and disperse, stirred at 50 rpm, heated to 100 ° C, and kept warm for 0.5 h to obtain an aqueous binder solution; the obtained aqueous binder solution was cooled to 57 ° C, stirred at 80 rpm, and 30 g of diisocyanate was added after the temperature stabilized. After keeping warm and stirring for 3 h, the temperature was lowered to 25 ° C, 15 g of azobiscyanovaleric acid ACVA (Shanghai Xinyu Biotechnology Co., Ltd.) and 15 g of maleic anhydride were added to prepare a modified binder; 6 kg of conductive carbon powder and 100 g of graphite were added to the prepared aqueous binder, and the carbon-coated slurry was prepared by stirring at about 4000 rpm and coated on the surface of pure aluminum foil. The water was removed through a coating and baking process to obtain a carbon-coated current collector product.
[0052] Comparative Example 1
[0053] 6 kg of polyacrylic acid was blended with 20 kg of deionized water to fully dissolve and disperse, stirred at 50 rpm, heated to 100 ° C, and kept warm for 0.5 h to obtain an aqueous binder solution; the obtained aqueous binder solution was cooled to 57 ° C, stirred at 80 rpm, kept warm and stirred for 3 h, then the temperature was lowered to 25 ° C, 15 g of azobiscyanovaleric acid ACVA (Shanghai Xinyu Biotechnology Co., Ltd.) and 15 g of maleic anhydride were added to obtain a modified binder; 6 kg of conductive carbon powder and 100 g of graphite were added to the prepared aqueous binder, and the carbon-coated slurry was prepared by stirring at about 4000 rpm and coated on the surface of pure aluminum foil. The water was removed through a coating and baking process to obtain a carbon-coated current collector product.
[0054] This comparative example is substantially the same as Example 1, except that no diisocyanate is added.
[0055] Comparative Example 2
[0056] 6 kg of polyacrylic acid was blended with 20 kg of deionized water to fully dissolve and disperse, the mixture was stirred at 50 rpm, the temperature was raised to 100°C, and the mixture was kept warm for 0.5 h to obtain an aqueous binder solution; the obtained aqueous binder solution was cooled to 57°C, the stirring speed was 80 rpm, 30 g of diisocyanate was added after the temperature stabilized, the mixture was kept warm and stirred for 3 h, the temperature was lowered to 25°C, and 15 g of maleic anhydride was added to obtain a modified binder; 6 kg of conductive carbon powder and 100 g of graphite were added to the prepared aqueous binder, the mixture was stirred at about 4000 rpm to obtain a carbon-coated slurry, which was coated on the surface of pure aluminum foil, and the moisture was removed through a coating and baking process to obtain a carbon-coated current collector product.
[0057] This comparative example is substantially the same as Example 1, except that azobiscyanovaleric acid ACVA is not added.
[0058] Comparative Example 3
[0059] 6 kg of polyacrylic acid was blended with 20 kg of deionized water to fully dissolve and disperse, the stirring speed was 50 rpm, the temperature was raised to 100 ° C, and the reaction was kept warm for 0.5 h to obtain an aqueous binder solution; the obtained aqueous binder solution was cooled to 57 ° C, the stirring speed was 80 rpm, and 30 g of diisocyanate was added after the temperature stabilized. After the reaction was kept warm and stirred for 3 h, the temperature was lowered to 25 ° C, and 15 g of azobiscyanovaleric acid ACVA (Shanghai Xinyu Biotechnology Co., Ltd.) was added to obtain a modified binder; 6 kg of conductive carbon powder and 100 g of graphite were added to the prepared aqueous binder, and the carbon-coated slurry was prepared by stirring at about 4000 rpm and coated on the surface of pure aluminum foil. The water was removed through a coating and baking process to obtain a carbon-coated current collector product.
[0060] This comparative example is substantially the same as Example 1, except that maleic anhydride is not added.
[0061] Comparative Example 4
[0062] 6 kg of polyacrylic acid was directly blended with 20 kg of deionized water to fully dissolve and disperse, the stirring speed was 50 rpm, the temperature was raised to 100°C, and the reaction was kept warm for 0.5 h to obtain an aqueous binder solution; the obtained aqueous binder solution was cooled to 57°C, stirred at 80 rpm, and kept warm for 3 h to obtain an aqueous binder; 6 kg of conductive carbon powder and 100 g of graphite were added to the prepared aqueous binder, and the carbon-coated slurry was prepared by stirring at about 4000 rpm and coated on the surface of the aluminum foil. The moisture was removed through a coating and baking process to obtain a carbon-coated current collector product.
[0063] The test steps of the embodiments and comparative examples are as follows:
[0064] Use a pole piece resistance meter to test the pole piece penetration resistance, and use a peeling force tester to verify the pole piece peeling force.
[0065] Among them, the sample width is 15mm, the sample length is 200mm, the peeling speed is 10mm / min, and the test tape is 3m double-sided tape.
[0066] The test results of the embodiments and comparative examples are shown in Table 1:
[0067] Table 1 Test results of embodiments and comparative examples
[0068]
[0069] The above test results show that:
[0070] The data show that this embodiment uses a modified aqueous binder to prepare a carbon-coated slurry, and the carbon-coated slurry is coated on the current collector foil to obtain a carbon-coated current collector, whose electrode peeling force is significantly improved, and the penetration resistance remains normal without significant changes. The effect of the embodiment of the present invention is significantly better than that of the comparative example.
[0071] The present invention introduces highly electronegative atoms through diisocyanate to form hydrogen bonds, and simultaneously forms covalent bonds by adding azobiscyanovaleric acid, thereby significantly improving the electrode peeling force after coating the carbon slurry and rolling, thereby effectively improving the cycle performance of the battery cell and the capacity retention rate of the battery cell, ensuring the uniformity of the positive electrode peeling force, and improving the electrical performance and life of the battery.
[0072] The present invention also strengthens the cross-linking reaction between diisocyanate, azobiscyanovaleric acid and the positive electrode sheet by adding a water-resistant additive, thereby synergistically improving the electrode sheet peeling force.
[0073] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, according to the technical essence of the present invention, any simple modification, equivalent replacement and improvement made to the above embodiment still falls within the protection scope of the technical solution of the present invention.
Claims
1. A current collector carbon coating slurry, characterized in that: The carbon coating slurry contains diisocyanate and azobiscyanovaleric acid.
2. The carbon coating slurry according to claim 1, characterized in that: The carbon coating slurry contains a binder, the diisocyanate and azobiscyanovaleric acid are added to the binder and the binder is mixed with the carbon coating material to obtain the carbon coating slurry; the carbon coating material is selected from at least one of conductive carbon powder and graphite.
3. A method for preparing a current collector carbon-coated slurry, characterized in that: The following steps are involved: Adding diisocyanate and azobiscyanovaleric acid into the binder aqueous solution to prepare a modified binder; The modified binder is mixed with a carbon-coated material to form a carbon-coated slurry.
4. The method for preparing the carbon coating slurry according to claim 3, characterized in that: The binder is selected from at least one of polyacrylic acid, styrene-butadiene latex, polyacrylonitrile and polyurethane. When preparing the binder aqueous solution, the binder and water are mixed in proportion and dispersed evenly, and heated and kept warm for reaction.
5. The method for preparing the carbon coating slurry according to claim 4, characterized in that: The mixing mass ratio of the binder to water is 2-5:10, and the heating and heat preservation reaction temperature is 80-100°C; after the binder aqueous solution is cooled to 50-70°C and the temperature is stable, diisocyanate is added, and the reaction is continued by heat preservation and stirring for 1-5 hours, and then the temperature is lowered to 20-30°C, and azobiscyanovaleric acid is added.
6. The method for preparing the carbon coating slurry according to claim 5, characterized in that: A water-resistant additive is also added to the binder aqueous solution, and the water-resistant additive is added after the azobiscyanovaleric acid is added; the mass percentage of the water-resistant additive added to the binder aqueous solution is 0.05-0.5%.
7. The method for preparing the carbon coating slurry according to claim 3, characterized in that: In the aqueous binder solution, the added mass percentage of diisocyanate is 0.1-5%, and the added mass percentage of azobiscyanovaleric acid is 0.05-0.1%; The mixing mass ratio of the binder to the conductive carbon powder and graphite is 20-50:30-60:0.1-2.
8. A carbon-coated current collector, characterized in that: The carbon-coated current collector has a carbon-coated layer formed on a current collector foil by a carbon-coated slurry prepared by the method described in claim 1 or 2 or any one of claims 3 to 7.
9. A positive electrode sheet, characterized in that: Containing the carbon-coated current collector according to claim 8.
10. A battery, characterized in that: A positive electrode sheet comprising the positive electrode sheet according to claim 9.